Employing reflective writing as a tool to enhance development of critical thinking skills among medical students - Shrivastava, Saurabh R; Bobhate, Prateek S; Inkane, Swapnil; Mendhe, Harshal G (Indian Journal of Community Health, 2025)
In medical education delivery, reflective writing is a process where medical students evaluate their thoughts and personal experiences. Critical thinking helps medical students and clinicians reach a provisional diagnosis, and decide about the management plans. Reflective writing encourages medical students to deeply analyze their clinical and learning experiences, and this entire process is vital for development of critical thinking skills. Acknowledging the need to train medical students in critical thinking, it is the need of the hour that teachers must explore and encourage students to reflect upon their learning experiences and in the process aid in the attainment of learning outcomes.